CaV3.2 drives sustained burst‐firing, which is critical for absence seizure propagation in reticular thalamic neurons. (21st February 2018) - Cain, Stuart M.; Tyson, John R.; Choi, Hyun‐Beom; Ko, Rebecca; Lin, Paulo J. C.; LeDue, Jeffrey M.; Powell, Kim L.; Bernier, Louis‐Philippe; Rungta, Ravi L.; Yang, Yi; Cullis, Pieter R.; O'Brien, Terence J.; et al.
Summary: Objective: Genetic alterations have been identified in the CACNA1H gene, encoding the CaV 3.2 T‐type calcium channel in patients with absence epilepsy, yet the precise mechanisms relating to seizure propagation and spike‐wave‐discharge (SWD) pacemaking remain unknown. Neurons of the thalamic reticular nucleus (TRN) express high levels of CaV 3.2 calcium channels, and we investigated whether a gain‐of‐function mutation in the Cacna1h gene in Genetic Absence Epilepsy Rats from Strasbourg (GAERS) contributes to seizure propagation and pacemaking in the TRN. Methods: Pathophysiological contributions of CaV 3.2 calcium channels to burst firing and absence seizures were assessed in vitro using acute brain slice electrophysiology and quantitative real‐time polymerase chain reaction (PCR) and in vivo using free‐moving electrocorticography recordings. Results: TRN neurons from GAERS display sustained oscillatory burst‐firing that is both age‐ and frequency‐dependent, occurring only in the frequencies overlapping with GAERS SWDs and correlating with the expression of a CaV 3.2 mutation‐sensitive splice variant. In vivo knock‐down of CaV 3.2 using direct thalamic injection of lipid nanoparticles containing CaV 3.2 dicer small interfering (Dsi) RNA normalized TRN burst‐firing, and in free‐moving GAERS significantly shortened seizures. Significance: This supports a role for TRN CaV 3.2 T‐type channels in propagating thalamocortical network seizures and setting the pacemaking frequency of SWDs.